Social Accountability Initiatives in Morocco, Tunisia, and Lebanon Civic Innovation in the Arab World After 2011 - Vloeberghs, Ward; Bergh, Sylvia I. (EADI Global Development Series,, 2024)
This Open Access Pivot represents the first extensive exploration of social accountability within the Arab world following the 2011 Arab uprisings. Drawing on insights from development studies, comparative politics, and Middle East studies, the authors explore the evolution of accountability as a governance concept, review theories on social accountability's role in improving public service delivery, and categorize types of social accountability initiatives, highlighting respective strengths and weaknesses. Detailed country chapters provide a solid basis for the comparative approach which reveals major variations in meanings of accountability, mobilization strategies, and official responses, rooted in the specific sociopolitical contexts of each country. Moreover, the book analyzes the influence of political and economic elites as well as the nature of popular mobilisation on accountability dynamics in the region. The authors conclude by discerning differences and commonalities across cases and offer recommendations for policymakers, donors, and practitioners seeking to enhance the effectiveness of social accountability initiatives. They address challenges such as the lack of enforcement mechanisms, the difficulty of scaling up initiatives, and the ambiguous effects of international interventions. This pioneering Pivot fills a significant void in the study of social accountability in the MENA region and provides a compelling framework for future research and policy design, making it an indispensable resource for experts and scholars. Ward Vloeberghs is Senior Lecturer in Political Science at Erasmus University College Rotterdam, the Netherlands, where he serves as Head of the Social and Behavioural Sciences Department. He researches (Arab) elites through their symbolic and material articulations of power. Sylvia I. Bergh is Associate Professor in Development Management and Governance at the International Institute of Social Studies (ISS), Erasmus University Rotterdam, and Senior Researcher at the Research Group Multilevel Regulation and the Centre of Expertise on Global and Inclusive Learning at The Hague University of Applied Sciences. She has published widely on state-society relations in the MENA region. .